2017
DOI: 10.1016/j.neurobiolaging.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of changes in neuronal function as a consequence of aging and tauopathic neurodegeneration using a novel and sensitive magnetic resonance imaging approach

Abstract: Tauopathies, the most common of which is Alzheimer’s disease (AD), constitute the most crippling neurodegenerative threat to our aging population. Tauopathic patients have significant cognitive decline accompanied by irreversible and severe brain atrophy, and it is thought that neuronal dysfunction begins years before diagnosis. Our current understanding of tauopathies has yielded promising therapeutic interventions but have all failed in clinical trials. This is partly due to the inability to identify and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…Immunohistochemical and biochemical examinations of postmortem rTg4510 brains confirmed that the progression of NFT formation was drastically increased from 4 months to 6 months of age [12,14,15,17]. Recently, advanced in vivo brain imaging techniques, including manganese-enhanced magnetic resonance imaging (MRI), arterial spin labeling, amide proton transfer imaging, diffusion tenser imaging, and PET, have enabled us to visualize neuronal dysfunction and pathological tau accumulation in living rTg4510 mice [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Immunohistochemical and biochemical examinations of postmortem rTg4510 brains confirmed that the progression of NFT formation was drastically increased from 4 months to 6 months of age [12,14,15,17]. Recently, advanced in vivo brain imaging techniques, including manganese-enhanced magnetic resonance imaging (MRI), arterial spin labeling, amide proton transfer imaging, diffusion tenser imaging, and PET, have enabled us to visualize neuronal dysfunction and pathological tau accumulation in living rTg4510 mice [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 94%
“…Recent advances in positron emission tomography (PET) imaging for tauopathy allow us to noninvasively examine the state of tau protein in living human brains [2][3][4][5][6][7]. Among potential tau PET tracers, 11 C-labeled phenyl/pyridinilbutadienyl-benzothiazoles/benzothiazolium 3 ([ 11 C] PBB3), [ 18 F]AV-1451, and [ 18 F]THKs have been used for pre-clinical studies in human brain imaging [6][7][8]. Among these tracers, PBB3 compound, based on a phenyl/pyridinil-butadienylbenzothiazoles/benzothiazolium (PBB) backbone compound, selectively binds to ␤-pleated sheet structures such as neurofibrillary tangles (NFTs), neuropil threads (NTs), and diffuse plaques, although selective binding to NFTs is much higher than the binding to plaques [2].…”
Section: Introductionmentioning
confidence: 99%
“…MEMRI can detect neuronal dysfunction at an early stage and contributes to early detection of the disease. Fontaine et al used a quantitative R1 value ( R1 = R1 6h -R1 baseline ) and intraperitoneal MnCl 2 injection to detect markedly abnormal elevations in R1 in the hippocampal CA1 and CA3 regions before the onset of cognitive deficits in tau protein transgenic mice (rTg4510) (97). In another AD model (5XFAD mice), MEMRI with SA of Mn 2+ showed increased signal intensity in brain areas associated with spatial cognition in the early stages of the disease (2-5 months of age); this increased intensity was associated with impaired learning and memory in behavioral tests (98).…”
Section: Neurodegenerative Diseases Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…P301S and P301L lines (transgenic for a human 4 repeat tau isoform) [6,[52][53][54], which have become important tools to study the mechanisms of abnormal tau aggregation and deposition in FTD (4 repeat tau) [61] and AD (3 and 4 repeat tau) [25, 33,41]. In the P301L 4 (Thy 1.2, pR5 line) [11,18], P301L (CaMKIIa) [23,43,62] and P301L (tetO) [14] mouse models, tau deposits begin forming before 3 months-of-age in neurons in the entorhinal cortex, hippocampus and later in the cortex, and amygdala; with neuroinflammation and impaired memory functions in hippocampus-and amygdala-dependent tasks manifesting at a later stage [49,50,67]. Brain atrophy and white matter changes indicating neurodegeneration were reported in P301L (CaMKIIa) mouse line around 9 months-of-age [16,23,43,62], which was driven by factors additional to human tau overexpression.…”
Section: Introductionmentioning
confidence: 99%